Clinical Characteristics and Prevalence of Celiac Disease in a Large Cohort of Type 1 Diabetes from Saudi Arabia - Mohammed Hakami; Saeed Yafei; Abdulrahman Hummadi; Raed Abutaleb; Abdullah Khawaji; Yahia Solan; Turki Aljohani; Ali Jaber Alhagawy; Amer Al Ali; Shakir Bakkari; Morghma Adawi; Maram Saleh; et al. (Medicina)
Background and Objectives: The link between celiac disease (CD) and type 1 diabetes (T1D) has been well-documented in the medical literature and is thought to be due to a shared genetic predisposition in addition to environmental triggers. This study aimed to determine the seroprevalence and biopsy-proven CD (PBCD) prevalence in individuals with T1D from Saudi Arabia and identify their clinical characteristics and the impact on glycemic control. Materials and Methods: A total of 969 children and adolescents with confirmed T1D were investigated. Prospective and retrospective data were collected to include clinical, anthropometric, and biochemical data. Total IgA and anti-TTG-IgA antibodies were screened to detect seropositive cases. Upper intestinal endoscopy and biopsy were performed to find BPCD. Results: The seroprevalence of CD was 14.6% (141/969), while BPCD prevalence was 7.5%. Females had a higher prevalence than males: 17.8% vs. 9.8%, p < 0.001. The CD group had lower HbA1c and more frequent hypoglycemia than the seronegative group. Conclusions: This study highlighted the high prevalence of CD in T1D Saudi patients. CD has multiple effects on glycemic control, growth, and puberty in children and adolescents with T1D. We emphasize the importance of early screening for CD at the time of diabetes diagnosis and periodically after that or if any atypical features present, especially anemia, growth delay, underweight, or frequent hypoglycemia.